(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The development of the business world is closely related to the marketing aspect. One of the culinary businesses that has unique characteristics and is popular is Warung Babi Guling. One of the famous suckling pigs in Bali is Warung Babi Guling Pan Ana. In 2022, Warung Babi Guling Pan Ana succeeded in increasing their net profit from 2021, but in 2023 there was a decline in sales from 2022. Apart from the data that has been described, researchers also conducted interviews regarding the Store Atmosphere at Warung Babi Guling Pan Ana and highlighted several negative aspect. The results of interviews conducted with several consumers who have never shopped at Warung Babi Guling Pan Ana often hear and receive negative information regarding the assessments given by customers who have shopped at Warung Babi Guling Pan Ana through reviews on social media. The population in this study is all consumers of Warung Babi Guling Pan Ana, the number of members of the population is not known for certain. The sampling technique was carried out using accidental sampling so that the researchers determined 104 samples. The analysis used in this research is multiple linear. These results show that Store Atmosphere, Electronic Word of Mouth, partially and simultaneously have a positive and significant effect on purchasing decisions at Warung Babi Guling Pan Ana.